Impact of Green Tea Catechin ECG and Its Synthesized Fluorinated Analogue on Prostate Cancer Cells and Stimulated Immunocompetent Cells - Stadlbauer, Sven; Steinborn, Carmen; Klemd, Amy; Hattori, Fumihiko; Ohmori, Ken; Suzuki, Keisuke; Huber, Roman; Wolf, Philipp; Gründemann, Carsten (Planta Medica, 2018)
Among the known or suspected risk factors, inflammation plays an important role in infectious and non-infectious pathways leading to cancer. Green tea polyphenols have been associated with reducing inflammation and protection against carcinogenesis, especially in prostate cancer. While most of the research in this field, so far, has focussed on epigallocatechin-3-O-gallate only, we studied epicatechin-3-O-gallate, the second most abundant green tea polyphenol with essential therapeutic potential, to obtain a more detailed understanding of its anti-tumor and anti-inflammatory action. Furthermore, to improve the bioactivity of (−)-epicatechin-3-O-gallate, we synthesized a difluoro analogue, called (−)-5,7-difluoro-epicatechin-3-O-gallate. Both compounds reduced cell proliferation of human primary inflammatory lymphocytes in an apoptosis-specific fashion, while (−)-5,7-difluoro-epicatechin-3-O-gallate had a significantly higher activity compared to the natural product (−)-epicatechin-3-O-gallate. Treatment of low-metastatic LNCaP and high-metastatic PC-3 prostate cancer cells with (−)-epicatechin-3-O-gallate and (−)-5,7-difluoro-epicatechin-3-O-gallate demonstrated a dose-dependent inhibition of cell viability in the low micromolar range. These effects suggest that (−)-epicatechin-3-O-gallate and the more effective (−)-5,7-difluoro-epicatechin-3-O-gallate could be therapeutically used to inhibit tumorigenesis during initiation, promotion, and progression by diminishing the amount of inflammation due to a reduction of inflammatory lymphocytes. Further studies are needed to prove this in in vivo experiments.
Keywords: Camellia sinensis; Theaceae; green tea polyphenols; fluorine analogue; prostate cancer; inflammation